2020
DOI: 10.1038/s41467-020-18531-4
|View full text |Cite
|
Sign up to set email alerts
|

Coastal flooding will disproportionately impact people on river deltas

Abstract: Climate change is intensifying tropical cyclones, accelerating sea-level rise, and increasing coastal flooding. River deltas are especially vulnerable to flooding because of their low elevations and densely populated cities. Yet, we do not know how many people live on deltas and their exposure to flooding. Using a new global dataset, we show that 339 million people lived on river deltas in 2017 and 89% of those people live in the same latitudinal zone as most tropical cyclone activity. We calculate that 41% (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 45 publications
0
86
0
Order By: Relevance
“…These are welcome additions to understanding populations at risk. New work has also examined aspects of the geography of LECZ, such as flooding in deltaic areas (Edmonds et al, 2020;Minderhoud et al, 2019) and modelling tidal heights (Muis et al, 2020;Taherkhani et al, 2020;Du et al, 2018;Pickering et al, 2017) and multiple stressors (Anderson et al, 2018;De Dominicis et al, 2020;Moftakhari et al, 2017) so relevant to improving estimates of coastal exposure itself. Along with improvements to understanding DEMs in urban areas 1340 (Pesaresi et al, 2021), these represent promising new avenues towards fuller understanding of seward hazards to town and city dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…These are welcome additions to understanding populations at risk. New work has also examined aspects of the geography of LECZ, such as flooding in deltaic areas (Edmonds et al, 2020;Minderhoud et al, 2019) and modelling tidal heights (Muis et al, 2020;Taherkhani et al, 2020;Du et al, 2018;Pickering et al, 2017) and multiple stressors (Anderson et al, 2018;De Dominicis et al, 2020;Moftakhari et al, 2017) so relevant to improving estimates of coastal exposure itself. Along with improvements to understanding DEMs in urban areas 1340 (Pesaresi et al, 2021), these represent promising new avenues towards fuller understanding of seward hazards to town and city dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…The Amazon delta (Figure 1) is unique in several ways: The inordinate size of the catchment to which it is connected and the massive sediment supply have led to the formation of the world's largest delta with significant hydrological, sedimentological, morphological, and ecological diversity. The sheer size of the delta has implied widely varying area estimates: 465,000 km 2 [6], 467,100 km 2 [7], 160,662 km 2 [2], and 85,667 km 2 [8]. In [2], the authors defined the delta area based on the intersection of biophysical and political-administrative boundaries, and suggested that the larger estimates may be due to the full inclusion of tidal channels and flats not directly connected to the main river and channel network.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Geomorphic area (defined as both land and water), habitable area (land area), and population increases in the Amazon delta [8], and 2020 population density [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…such as fluid withdrawal, increases the relative sea level rise of these coastal landscapes. Reductions in sediment supply due to upstream levees and dams lessen mitigation of subsidence [6], with an estimated 25 million people living on sediment-starved deltas [7]. Although 11,000 deltas globally have experienced net land gain over the past 30 years from increases in river fluvial sediment content from deforestation, as well as redistribution of sediments on deltas transitioning toward increasingly tide-dominated, these gains are not expected to be sustained under rising sea level conditions [8][9][10][11] and projected declines in fluvial sediment delivery [12].…”
Section: Introductionmentioning
confidence: 99%